Sports festival for kids with down syndrome - Maulana, Vistor Syapri; Sumaryanti, Sumaryanti; Mulyawan, Rizki; Delano, Enggista Hendriko; Rahayu, Atikah (Universitas Negeri Yogyakarta, 2025)
This Community Service activity aims to increase the knowledge and skills of Downsyndrome children in exercising. This community service activity also improves the cognition of downsyndrome children to be better by doing sports activities. This activity can be a talent guide for downsyndrome children in the field of sports. This activity is composed of several posts that can hone downsyndrome children in terms of cognition with activities Arranging puzzles and matching shapes. To improve skills with posts to enter the ball, move the ball and kick the ball. This activity was carried out for 1 day on Saturday, July 27, 2024 at 08.00-11.30 which was attended by 30 downsyndrome child participants. This activity was carried out at the Yogyakarta State University Community Sports Park (TOM). It is hoped that after the activity is completed, good cooperation can be established to explore the potential of downsyndrome children in increasing knowledge and skills in sports.